Design of Cyclodextrin-Based Functional Systems for Biomedical Applications - Xu, Wanjia; Li, Xiumei; Wang, Liang; Li, Siyuan; Chu, Shengnan; Wang, Jiachun; Li, Yijia; Hou, Jinxing; Luo, Quan; Liu, Junqiu (Frontiers in Chemistry, 2021)
Cyclodextrins (CDs) are a family of α-1,4-linked cyclic oligosaccharides that possess a hydrophobic cavity and a hydrophilic outer surface with abundant hydroxyl groups. This unique structural characteristic allows CDs to form inclusion complexes with various guest molecules and to functionalize with different substituents for the construction of novel sophisticated systems, ranging from derivatives to polymers, metal-organic frameworks, hydrogels, and other supramolecular assemblies. The excellent biocompatibility, selective recognition ability, and unique bioactive properties also make these CD-based functional systems especially attractive for biomedical applications. In this review, we highlight the characteristics and advantages of CDs as a starting point to design different functional materials and summarize the recent advances in the use of these materials for bioseparation, enzymatic catalysis, biochemical sensing, biomedical diagnosis and therapy.